Understanding Students’ Experiences with Project-Based Assessment across Educational Levels and Contexts - Radita, Cindy; Widiati, Utami; Hayati, Nur (Journal of Language and Literature Studies, 2025)
Project-based assessment (PBA) is often highlighted as a more authentic, engaging, practical, and student-centered approach compared to traditional exams. However, despite its growing use, there is limited and unified understanding of how students actually experience PBA across different educational levels and learning contexts. This gap in the literature is crucial, as student experiences are central to determining the effectiveness and inclusiveness of assessment practices in diverse classroom settings. It is crucial to understand how students experience PBA to ensure that this assessment approach fulfills its potential of meaningful, equitable, and effective learning. This article aims to systematically review empirical studies that explore students’ experiences with PBA, focusing on how these experiences vary across primary, secondary, and tertiary education as well as cultural and institutional contexts. The study is grounded in qualitative data drawn from published research articles, analyzed using thematic synthesis under the PRISMA framework. Inclusion criteria targeted peer-reviewed studies that foreground student voices and were published within the last 10 years. Findings indicate a combination of positive experiences, such as increased engagement, collaboration, and real-world skill development, alongside persistent challenges, including perceived workload imbalance and unclear assessment criteria. The review underscores the significance of adapting PBA to specific contexts and advises that future research systematically include student perspectives to refine assessment methods better and promote fairness. Implications of these findings for practice for educators and policy makers are that more nuanced and responsive assessment strategies have the potential to improve inclusiveness and instruction. Future research should also look into how school support, teacher support, and cultural contexts influence the efficacy of PBA interventions.